Multiple Heterohelicenes: Synthesis, Properties and Applications - Yang, Wen‐Wen; Shen, Jun‐Jian (Chemistry : a European journal, 2022)
Multiple heterohelicenes are a unique class of helical nonplanar scaffolds that have attracted great attention due to their appealing shapes, optical and electronic properties, and potential applications in chiral materials. This review describes the recent advances and challenges in the design and synthesis of representative multiple heterohelicenes with intriguing chiral properties. And the corresponding applications are also covered. Multiple heterohelicenes represent an important class of materials for chiral optical and electronic devices. This review provides a summary of the recent advances in the precision synthesis and characterization of multiple heterohelicenes, as well as an outlook on multiple heterohelicene chemistry and the further molecular design of highly multiplexed heterohelicenes.